The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/su8090903
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Land Governance for Eco-Urbanization

Abstract: "Eco-urbanization" emphasizes the importance of the ecological and environmental aspects of urbanization, which is to approach a balanced and healthy ecosystem through paying attention to the ecological intercorrelation of many factors. This involves balancing the stocks and utilization of multi-resources and balancing the efficiency and equality of multi-resources allocation to improve the quality of life for both urban and rural areas. In this dynamic process, resource allocations are carried out at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Li et al (2019) combined qualitative and quantitative analysis techniques and a broad hierarchical structure to give an evaluation system for sponge cities [16]. Wang et al (2016) studied the connotation and construction methods of sponge city and believed that we should be paid to the individual heterogeneity of the city in construction [17]. Zhou et al (2022) analyzed the distribution of extreme precipitation in China, and found that extreme precipitation in China showed obvious differences due to different geographical locations [18].…”
Section: Literaturementioning
confidence: 99%
“…Li et al (2019) combined qualitative and quantitative analysis techniques and a broad hierarchical structure to give an evaluation system for sponge cities [16]. Wang et al (2016) studied the connotation and construction methods of sponge city and believed that we should be paid to the individual heterogeneity of the city in construction [17]. Zhou et al (2022) analyzed the distribution of extreme precipitation in China, and found that extreme precipitation in China showed obvious differences due to different geographical locations [18].…”
Section: Literaturementioning
confidence: 99%
“…It should be noted that from step 8 to step 10, this is an iterative calculation process and the centre of the cluster is constantly updated and the distance of the data is calculated, until the centre of the cluster and the clustering result do not change significantly. (11) In this step, we have completed the whole process of clustering calculation and obtained stable clustering results. We also output the results of clustering.…”
Section: Construction Of Modelmentioning
confidence: 99%
“…These problems have caused serious external problems and restricted the healthy development of urban economy and society [8,9]. City is the engine of economic growth, the high quality of the ecological environment is the intrinsic motivation of urban economic growth, therefore, establishing and improving the ecological environment management system and focusing on solving the problem of urban ecological environment, especially for China with the increasing population and urbanization level, become the inevitable choice of sustainable development of social economy [10,11]. In 2013, to solve the serious urban water environment problems, the Chinese government put forward the sponge city strategy, which is an urban stormwater management system that enables the city to absorb and save the stormwater like a sponge and release the reserved water for use when the city is short of water, so that the sponge city can play an important role in the sustainable development of cities [12].…”
Section: Introductionmentioning
confidence: 99%
“…LULC changes extensively occur during agricultural activities (e.g., deforestation for agricultural expansion and land management) [1][2][3], resource mining activities [4,5], and urbanization [6,7]. As a crucial driver of environmental change, LULC changes can contribute to climate change, soil erosion, and biodiversity loss by altering the carbon cycle and soil quality [8][9][10][11][12], and thus can affect soil functionality and deteriorate ecosystem services [13].…”
Section: Introductionmentioning
confidence: 99%